The prevalence of EGFR mutations in non‐small cell lung cancer in an unselected Caucasian population. Issue 2 (25th November 2014) - Skov, Birgit G; Høgdall, Estrid; Clementsen, Paul; Krasnik, Mark; Larsen, Klaus Richter; Sørensen, Jens Benn; Skov, Torsten; Mellemgaard, Anders
<x xml:space="preserve">Abstract</x> EGFR mutation frequencies in unselected Caucasian populations are unknown. This study assesses the prevalence of EGFR mutations in an unselected population‐based cohort, and the correlation between mutation and gender, age, ethnicity, smoking habits, and pathological data. NSCLC patients diagnosed in a well‐defined Danish population were included. The type of the diagnostic material, and data on smoking were registered. The mutation analyses were investigated by Therascreen EGFR RGQ‐PCR Kit or Sanger sequencing. A total of 658 men and 598 women were included. 6.2% were never smokers, 38.9% were ex‐smokers, and 54.9% were current smokers. One thousand one hundred and sixty‐one (92.4%) patients had sufficient material for mutation analysis. Cytological material was used for 38% of the mutation analyses. 5.4% had mutation in the EGFR gene (4.3% men/6.7% women). 87% were activating mutations. 8.0% of adenocarcinomas, and 1.9% of squamous cell carcinomas were mutated. 29.4%, 4.4% and 2.9% of never, ex‐ and current smokers were mutated (p < 0.001). No difference in mutation rate was observed between patients with cytology only, histology only or both cytology and histology available. 5.4% of the patients had EGFR mutation. Adenocarcinomas were mutated more often (8.0%) than squamous cell carcinomas (1.9%). Mutations were found in never smokers as well as in former and current smokers. No difference in gender and age regarding mutation status was observed. EGFR mutations analysis was possible in almost all patients with no difference between cytology and histology specimens.